The end of work is near, isn't it?: survey evidence on automation angst - Arntz, Melanie; Blesse, Sebastian; Doerrenberg, Philipp (Discussion paper, 2022)
We study the extent of automation angst and its role for policy preferences, labor market choices and real donation decisions using a customized survey in Germany and the US. We first document that a majority perceives automation as a major threat to overall employment and as a cause of rising inequality, whereas less than a third is concerned about their own labor-market prospects. We find evidence that automation angst is strongly associated with people's trust in governments and general political beliefs, especially in the US. At the same time, automation angst is associated with preferences for more policy interventions and also relates to stated and actual behavior. Using randomized survey experiments, we find that scientific information about zero net employment effects of automation, on average, reduce related concerns. Yet, treatment responses are multidimensional and depend on prior beliefs about the future or work. This translates into heterogeneous and sometimes even opposing effects on policy preferences and individual behavior.
Keywords: Graue Literatur